Analysis of Organisational Performance Utilizing the Balanced Scorecard Approach - Kurniawan, Hendra (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The objective of this study is to evaluate the performance of PT Angkasa Pura II using the balanced scorecard methodology. According to the Slovin formula, there were 98 employees in the sample size. The essential data included in this study was gathered by distributing questionnaires to all participants. The SPSS version 23 software for the Windows operating system facilitates the use of multiple regression as the data analysis technique in this study. Furthermore, the study also included descriptive statistical analysis. This analysis encompassed doing classical assumption tests, which consisted of normality testing, heteroscedasticity testing, and multicollinearity testing. Additionally, all hypotheses underwent partial, simultaneous, and coefficient of determination tests. The findings of this study suggest that the financial, customer, internal business, and growth and learning perspectives collectively and partially exert a favorable and statistically significant impact on the performance of PT Angkasa Pura II (Persero).